Getting started with open source technologies : applying open source technologies with projects and real use cases - Rathee, Sachin; Chobe, Amol (Apress L. P., 2022)
Using real life examples, learn how open source projects are consumed and explore the nuances within different industries in adopting open source technologies. After gaining a basic understanding of open source and open standards, understand how licensing helps turn community code into an enterprise worthy component. It also helps you understand future governance of the open source software. Once in effect, continuous security becomes a challenge for open source components so we'll examine its ongoing security aspects. This book will also cover different open source domains and industries and discuss how an enterprise can transform itself by applying key open source principles. In the end Getting Started with Open Source Technologies will provide a 360-degree view of open source and show you how to apply it. What You'll Learn Understand current trends in open source and why it is relevant today Gain entry into the open source world to properly license your source code Review open source usage within different industries and apply the learnings to your enterprises Evangelize and create advocates in open source communities Who This Book Is For Enterprises (Developers/Operators/Management) and academics who want to get a 360-degree view of open source no matter how early or advanced they are in their adoption of any open source technology.